Hydrogenation of allyl alcohols catalyzed by aqueous palladium and platinum nanoparticles1. Issue 84 (16th September 2015) - Di Pietrantonio, Krystel; Coccia, Francesca; Tonucci, Lucia; d'Alessandro, Nicola; Bressan, Mario
<x xml:space="preserve">Abstract</x> Hydrogenations of allyl alcohols in aqueous media, at room temperature and pressure, were performed in presence of Pd or Pt lignin nanoparticles as catalysts to obtain saturated alcohols.